Joe Somebody - Kopelson, Arnold; Kopelson, Anne.; Gross, Matthew; Atchity, Kenneth John.; Reilly, Brian; Pasquin, John.; Shepherd, John Scott; Allen, Tim, 1953-; Bowen, Julie; Lynch, Kelly, 1959-; Germann, Greg.; Panettiere, Hayden; et al. (Beverly Hills, Calif. : Twentieth Centry Fox Home Entertainment, 2002)
Joe Scheffer is a mild-mannered single dad who's overworked and underappreciated at the office. But when the company bully knocks him down in front of his daughter, this Nobody decides to become Joe Somebody and kick some butt!
Double sided.
Originally produced as a motion picture in 2001.
Includes widescreen and fullscreen versions.
Special features: producer and director commentary; fight choreography featurette; 4 deleted scenes with optional commentary; theatrical trailer.
Director of photography, Daryn Okada ; editor, David Finfer ; music, George S. Clinton ; production designer, Jackson de Govia.
Tim Allen, Julie Bowen, Kelly Lynch, Gregg Germann, Hayden Penetierre, Patrick Warburten, Jim Belushi.
Keywords: Self-defense -- Drama; Comedy films; Video recordings for the hearing impaired; Video recordings; DVD-Video discs; DVDs